Directly Converted Human Fibroblasts Mature to Neurons and Show Long-Term Survival in Adult Rodent Hippocampus - Natalia Avaliani; Ulrich Pfisterer; Andreas Heuer; Malin Parmar; Merab Kokaia; My Andersson (Stem Cells International)
Direct conversion of human somatic cells to induced neurons (iNs), using lineage-specific transcription factors has opened new opportunities for cell therapy in a number of neurological diseases, including epilepsy. In most severe cases of epilepsy, seizures often originate in the hippocampus, where populations of inhibitory interneurons degenerate. Thus, iNs could be of potential use to replace these lost interneurons. It is not known, however, if iNs survive and maintain functional neuronal properties for prolonged time periods in in vivo. We transplanted human fibroblast-derived iNs into the adult rat hippocampus and observed a progressive morphological differentiation, with more developed dendritic arborisation at six months as compared to one month. This was accompanied by mature electrophysiological properties and fast high amplitude action potentials at six months after transplantation. This proof-of-principle study suggests that human iNs can be developed as a candidate source for cell replacement therapy in temporal lobe epilepsy.